(untitled) (PAAN Journal, 2025)
The relationship between political leadership and administration has been debated in public administration. Based on the review of extant literature, this article examines the relationships between politics and administration. It is worth noting that despite being distinctive, their relationships are an evolving and dynamically interactive process in contemporary governance. Therefore, it is unwise to overlook their constant cross-cutting engagements, power relations in politics, and the administration’s influence in policy making. Against this backdrop, this article underscores the need to move beyond the simplistic dichotomy of the political and administrative spheres to understand the distinctive logic that shape political and administrative behaviour.